Exploring Relationships Among Occupational Safety, Job Turnover, and Age Among Home Care Aides in Maine. (February 2018) - Butler, Sandra S.
As the U.S. population ages, the number of people needing personal assistance in the home care setting is increasing dramatically. Personal care aides and home health workers are currently adding more jobs to the economy than any other single occupation. Home health workers face physically and emotionally challenging, and at times unsafe, work conditions, with turnover rates ranging from 44 percent to 65 percent annually. As part of a mixed-method, longitudinal study in Maine examining turnover, interviews with 252 home care aides were analyzed thematically. Responses to interview questions regarding the job's impact on health and safety, the adequacy of training, and the level of agency responsiveness were examined. Emergent themes, indicating some contradictory perspectives on workplace safety, quality of training, and agency support, were compared across three variables: job termination, occupational injury, and age. Implications for increasing occupational safety and job retention are discussed.